MENAKAR DALUWARSA: Kajian Perbandingan Daluwarsa Pemalsuan Surat Dalam Pembaharuan Hukum Pidana - Chandra, Tofik Yanuar; Hajairin, Hajairin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
Comparative study of the expiration of mail forgery in Law No. 1/1946 on Criminal Code and Law No. 1/2023 on Criminal Code. This comparative study is intended to understand the differences and similarities of expiration in the prosecution of criminal cases, so that expiration can be a legal instrument that can realize justice for all parties to criminal cases. The method used is normative legal research, normative legal research is also to inventory positive law, find legal principles and doctrines, synchronize existing laws and regulations and conduct research by studying and examining and tracing various existing literature. With several approaches, namely the Legislative Approach, Historical Approach, Comparative Approach and Conceptual Approach. The findings in the results of this study are a comparative study of the expiration of mail forgery, in Law/1/1946 / Criminal Code and Law/1/2023 / Criminal Code it can be concluded that the authority to prosecute a criminal offender can be abolished regulated in Article 78 paragraph (1) of the Criminal Code, regarding Forgery in general is regulated in Article 263 paragraph (1) of the Criminal Code. After the reform of criminal law, the authority to prosecute is declared void due to expiration is regulated in Article 163 of Law No. 1/2023 / Criminal Code, but regarding the explanation of the offense of forgery of letters is contained in Articles 391 and 392 of Law No. 1/2023 / Criminal Code. Comparison of the expiration of mail forgery in the Criminal Code and the New Criminal Code from the aspect of offense formulation and expiration limitation is very different, but there is a similarity in placing the object that can be subject to the crime of mail forgery, namely a person who makes a fake letter and uses a fake letter.